Determining the Temporal Profile of Intracranial Pressure Changes Following Transient Stroke in an Ovine Model - Sorby-Adams, Annabel J.; Leonard, Anna V.; Elms, Levi E.; Marian, Oana C.; Hoving, Jan W.; Yassi, Nawaf; Vink, Robert; Thornton, Emma; Turner, Renée J. (Frontiers in Neuroscience, 2019)
Background and Purpose: Cerebral edema and elevated intracranial pressure (ICP) are the leading cause of death in the first week following stroke. Despite this, current treatments are limited and fail to address the underlying mechanisms of swelling, highlighting the need for targeted treatments. When screening promising novel agents, it is essential to use clinically-relevant large animal models to increase the likelihood of successful clinical translation. As such, we sought to develop a survival model of transient middle cerebral artery occlusion (tMCAO) in the sheep and subsequently characterize the temporal profile of cerebral edema and elevated ICP following stroke in this novel, clinically-relevant model. Methods: Merino-sheep (27M;31F) were anesthetized and subject to 2 hours tMCAO with reperfusion or sham surgery. Following surgery, animals were allowed to recover and returned to their home pens. At preselected times points ranging from 1 to 7 days post-stroke, animals were re-anesthetized, ICP measured for 4 hours, followed by imaging with MRI to determine cerebral edema, midline shift and infarct volume (T2, FLAIR, DWI). Animals were subsequently euthanized and their brain removed for immunohistochemical analysis. Serum and cerebrospinal fluid samples were also collected and analyzed for substance P (SP) using ELISA. Results: ICP and MRI scans were normal in sham animals. Following stroke, ICP rose gradually over time and by 5 days was significantly (p<0.0001) elevated above sham levels. Profound cerebral edema was observed as early as 2 days post-stroke and continued to evolve out to 6 days, resulting in significant midline shift which was most prominent at 5 days post-stroke (p<0.01), in keeping with increasing ICP. Serum SP levels were significantly elevated (p<0.01) by 7 days post tMCAO. Conclusion: We have successfully developed a survival model of ovine tMCAO and characterized the temporal profile of ICP. Peak ICP elevation, cerebral edema and midline shift occurred at day 5-6 following stroke, accompanied by an elevation in serum SP. Our findings suggest that novel therapeutic agents screened in this model targeting cerebral edema and elevated ICP would most likely be effective when administered prior to 5 days, or as early as possible following stroke onset.